Electronic Screen syndrome (ESS): An emerging disorder, an important and influential structure on children’s neuro-developmental disorders - Ahmadi, Sedigheh (Iranian Journal of Neurodevelopmental Disorders, 2023)
Purpose: Research shows that early and excessive exposure to screens is related to negative health and developmental consequences of children. Since in Iran, there were no sources and research background about Electronic Screen Syndrome (ESS), the purpose of this research is to introduce this emerging disorder and its role in causing or aggravating neuro-developmental disorders in children. Method: The study method was a systematic review and related sources and researches from 2000 to 2023 were extracted using various reliable scientific databases. Those sources that matched the criteria of the research and the main keywords of the research were included in the study (71 sources) and unrelated sources (25 sources) were excluded. The literature on the effects of early and uncontrolled exposure of young children to electronic screens was critically reviewed. Findings: The findings of various researches showed that the syndrome of electronic screens with children’s developmental and psychological disorders (hyperactivity / attention deficit, reading and writing problems and learning disorders, autism spectrum disorders, problems related to language development, communication and behavioral problems,....) is related and can cause and aggravate these disorders and problems. Conclusion: The results of this study will be very significant in order to inform therapists, parents and trainers, health officials of the country for prevention, education and treatment